AN ANALYSIS OF EMPLOYING RUNNING DICTATION GAME TO ENHANCE THE STUDENTS' ENTHUSIASM IN LEARNING DICTATION - Agus - Rahmat (British (Jurnal Bahasa dan Sastra Inggris), 2023)
The objectives of this research were to find out the effectiveness of running dictation game to enhance the students’ enthusiasm and the students’ perspective toward the strengths and the weaknesses of running dictation game in learning dictation. The researcher employed descriptive qualitative research design and the instruments was self-report questionnaire. There are ten informants of this research was the college students from Makassar, South Sulawesi. The researcher chose the informants randomly after the running dictation game in learning dictation was applied. The result of this research were running dictation game was effective to enhance the students’ Enthusiasm in learning dictation with various kinds of reasons. The reasons were running dictation game can train their ability to recall the sentences, the compactness of the group, this activity is comfortable, interactive and enjoy to be applied in learning dictation so that they are enthusiastic to follow the lesson, and it involves three skills in English such as listening, writing and speaking skill. The strengths of running dictation game based on the informants’ perspectives are this game can train the ability to recall/memorize the sentences and the compactness of the team in the group, this activity can improve some skills in English such as listening, writing and speaking skills. This running dictation game is fun, interested and it does not make boring and sleepy in learning process. Whereas the weaknesses based on the informants’ perspective of running dictation games were the time is less and the sentence is too long as well as the facility to run the game is not adequate. The use of this game was effective but the teachers or the lecturers have to adjust the level of vocabulary and the use of time in the learning process.